AUTHORITY, HERMENEUTICS, AND BEAUTY, TELAAH GAGASAN KHALED ABOU EL FADL TENTANG METODOLOGI HUKUM ISLAM - Toriqirrama, Faby (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyse the concepts of authority, hermeneutics, and beauty in the thought of Khaled Abou El Fadl and their implications for Islamic law in Indonesia. The research employs a qualitative approach with the library research method. Data is obtained from various literary sources, including books, scholarly journals, and relevant articles. The analysis is conducted using a descriptive-analytical method by describing and examining El Fadl’s thoughts and linking them to the context of Islamic law in the contemporary era. The findings indicate that the concept of authority in Islamic law should reflect ethical and moral values that prevent the monopolisation of religious understanding. El Fadl’s hermeneutics emphasise openness in interpreting sacred texts, while the concept of beauty highlights that Islamic legal rulings should embody justice and moral aesthetics. The study concludes that El Fadl’s ideas offer new insights into the development of a more contextual, humanistic, and responsive methodology of Islamic law. The concepts he proposes are relevant in constructing a more inclusive Islamic legal system that prioritises human values. Keywords: El Fadl; authority; hermeneutics; beauty